Agromyces and Arthrobacter isolates from surficial sediments of the Passaic River degrade dibenzofuran, dibenzo-p-dioxin and 2-monochlorodibenzo-p-dioxin. Issue 3 (3rd July 2021) - Almnehlawi, Haider S.; Dean, Rachel K.; Capozzi, Staci L.; Rodenburg, Lisa A.; Zylstra, Gerben J.; Fennell, Donna E.
Abstract: The Passaic River in New Jersey, USA is heavily polluted by chlorodibenzo- p -dioxins (CDDs). Highly chlorinated CDDs are dechlorinated by anaerobic bacteria from these sediments, producing lightly chlorinated or even non-chlorinated dibenzo- p -dioxin (DD) daughter products. Surficial Passaic River sediments were enriched under aerobic conditions and three bacterial strains (PR1, PR2 and PR3) were isolated using dibenzofuran (DF) as a model substrate. PR1 is closely related to Janibacter terrae (99.4%), a known CDD and DD degrader. PR2 and PR3 are closely related to Agromyces mediolanus (99.2%) and Arthrobacter oryzae (99.5%), respectively, which are genera not known to degrade CDDs. Janibacter PR1 grew more rapidly on DF than PR2 and PR3. The less well characterized PR2 and PR3 both degraded DD and 2-monochlorodibenzo- p -dioxin (2MCDD), at similar rates. Neither PR2 nor PR3 transformed 2, 7-dichlodibenzo- p -dioxin (2, 7DCDD). An angular dioxygenase 99.7% identical to that in Terrabacter sp. DBF63 was detected by PCR in Janibacter PR1 and Agromyces PR2. PCR did not detect an angular dioxygenase in Arthrobacter PR3. In this work, novel aerobic bacterial strains that can aerobically degrade the products of dechlorination were identified in surficial Passaic River sediments. The presence of these bacteria could enable an in situ treatment process that completely removes all CDDs from the sediment.